2016
DOI: 10.1016/j.earlhumdev.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Very low birth weight infants in China: the predictive value of the motor repertoire at 3 to 5months for the motor performance at 12months

Abstract: BackgroundStudies on motor performance and its early markers are rare in China, especially in very low birth weight (VLBW) infants.ObjectiveApart from the assessment of the inter-scorer agreement, we aimed to analyze to what extent the motor repertoire at 10 to 18 weeks postterm was related to neonatal complications, and gross and fine motor performance at 12 months after term.Study designExploratory prospective study.SubjectsSeventy-four VLBW infants (58 males; mean gestational age = 29 weeks; mean birth weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
5
32
0
Order By: Relevance
“…Another study on VLBW infants and their GM was recently conducted in India, applying both visual perception-based and computer-based GMA 2 . Similar to Zang et al 51 , the Indian study showed that absent or abnormal FM and a monotonously abnormal movement character was associated with lower motor quotients at 12 months corrected age. The computer-based GMA confirmed that the variability of the spatial center of motion was higher – thus indicating absent FM – in children with lower motor quotients 2 .…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Another study on VLBW infants and their GM was recently conducted in India, applying both visual perception-based and computer-based GMA 2 . Similar to Zang et al 51 , the Indian study showed that absent or abnormal FM and a monotonously abnormal movement character was associated with lower motor quotients at 12 months corrected age. The computer-based GMA confirmed that the variability of the spatial center of motion was higher – thus indicating absent FM – in children with lower motor quotients 2 .…”
Section: Introductionsupporting
confidence: 73%
“…In Asia, three Chinese studies 32 , 49 , 51 , one study conducted in India 2 , and one Iranian study 45 met the inclusion criteria. Yang et al 49 conducted a longitudinal assessment in a large number of children, confirming that the absence of FM was a significant marker of CP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motor repertoire of infants at 3–5 months consists not only of fidgety movements but also of other movements such as antigravity movements to the midline and legs lift, kicking, swiping, or wiggling-oscillating limb movements [13]. A detailed assessment of these age-specific movements including fidgety movements and several postural patterns was proposed in 2004 [5] and has been applied to several high-risk groups (e.g., [6,14,15,16]) but also to typically developing infants [6,17,18]. The scoring is based on the optimality concept [19], with the advantage that its semi-quantitative approach documents small changes in an otherwise categorically assessed motor behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The scoring is based on the optimality concept [19], with the advantage that its semi-quantitative approach documents small changes in an otherwise categorically assessed motor behavior. Some of the studies applying this approach revealed that a reduced score was associated with motor and language dysfunction at toddler age [6,15], minor neurological dysfunctions [20], or learning difficulties at school age [21]. Two other studies [22,23] showed that such a detailed assessment of early movements and postures helps to predict the level of self-mobility in children with CP.…”
Section: Introductionmentioning
confidence: 99%